Luminal and mucosal-associated intestinal microbiota in patients with diarrhea-predominant irritable bowel syndrome - Ian M. Carroll; Young-Hyo Chang; Jiwon Park; R. Balfour Sartor; Yehuda Ringel (2010)
Recent studies have suggested a role for an altered intestinal microbiota in the pathophysiology of irritable bowel syndrome (IBS). However, no consensus has been reached regarding the association between specific enteric bacterial groups and IBS. The aim of this study was to investigate the fecal and mucosal-associated microbiota using two independent techniques in intestinal samples from diarrhea-predominant IBS (D-IBS) and healthy controls.Fecal and colonic mucosal biopsy samples were obtained from 10 D-IBS patients and 10 healthy controls. Colonic tissue was collected during a un-sedated un-prepped flexible sigmoidoscopy. Fecal and tissue samples were processed immediately upon collection for culture under aerobic and anaerobic conditions or frozen for further molecular analysis. DNA was extracted from all frozen samples and used to enumerate specific bacterial groups using quantitative real-time PCR (qPCR).Culture analysis of intestinal samples demonstrated a significant reduction in the concentration of aerobic bacteria in fecal samples from D-IBS patients when compared to healthy controls (1.4 × 107 vs. 8.4 × 108 CFUs/g feces, P = 0.002). qPCR analysis demonstrated a significant 3.6 fold increase (P = 0.02) in concentrations of fecal Lactobacillus species between D-IBS patients and healthy controls.Our culture and molecular data indicate that quantitative differences exist in specific bacterial groups in the microbiota between D-IBS and healthy subjects.